Field notes contributed by Ronald Harms, winter 1982-1983 - Harms, Ronaldet al (1982)
Winter report of birds found in northwest Iowa contributed by Ronald Harms. Also included is a brief note from Harms to Thomas H. Kent about a Snowy Owl sighting. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed/flatbed